Laboratory methods to simulate the mechanical degradation of resin composite restorations. Issue 1 (January 2022) - Lima, Veronica P.; Machado, Jaqueline B.; Zhang, Yu; Loomans, Bas A.C.; Moraes, Rafael R.
Highlights: Varied in vitro devices simulate mechanical degradation of composite restorations. High heterogeneity across methods and test conditions was observed. Reporting problems were observed in this sample of 49 articles. The overall evidence suggested a lack of clinical validation of research methods. Comparability of findings among different oral simulation approaches is unknown. Graphical Abstract: ga1 Abstract: Objectives: This study reviewed the literature to identify in vitro approaches that have been used to simulate the mechanical degradation and fatigue of resin composite restorations. Methods: A search for articles was carried out in 4 databases and included studies in which composite restorations were bonded to teeth and subject to cyclic loading. Articles were assessed for eligibility, and the following items were the extracted from the included studies: authors, country, year, materials tested, simulation device and details including load magnitude and frequency, number of cycles, type of antagonist, test medium, and temperature. Data were analyzed descriptively. Results: The 49 studies included showed a high level of heterogeneity in methods, devices, and test parameters. Nineteen different simulation devices were used, applying loads varying between 30 and 2900 N, and frequencies varying between 0.4 and 12 Hz. The load and frequency used most often were 50 N (63.3%) and 1.5–1.7 Hz (32.7%). The number of cycles varied between 10 K and 2.4 M, 1.2 M was the most prevalent (40.8%). The majority of studies combined cyclic loading with at least one additional aging method: static liquid storage, thermo-mechanical cycling applied simultaneously, and thermal cycling as a discrete aging step were the three most frequent methods. The overall evidence indicated reporting problems, and suggested a lack of clinical validation of the research methods used. Significance: Validation studies, underlying clinical supporting data, and better reporting practices are needed for further improving research on the topic. Specific suggestions for future studies are provided.